Application of Problem-Based Learning to Enhance Mathematical Reasoning Skills of Phase E Students in Class X-3 SMAN 6 Pekanbaru - Purba, Ira Devi Anna; Maimunah, Maimunah; Kartini, Kartini (Journal of Educational Sciences, 2025)
This study aims to enhance the learning process and improve students' Mathematical Reasoning Skills (MRS) through the implementation of the Problem-Based Learning (PBL) model. The initial MRS test results for Class X-3 at SMAN 6 Pekanbaru were relatively low, with an average score of 46.07%. This was attributed to students' unfamiliarity with reasoning-based questions, insufficient understanding of the material, and a learning process that failed to actively engage students. The research, conducted as classroom action research, consisted of two cycles involving 35 students during the first semester of the 2024/2025 academic year, focusing on sequences and series topics. Research instruments included teaching modules and student worksheets, along with observation sheets and MRS tests for data collection. Qualitative data from observations indicated a progressive improvement in learning quality across meetings, with students becoming more active and capable of constructing their knowledge. Quantitative data from the MRS tests showed an N-Gain score improvement from 0.44 in the first cycle to 0.68 in the second cycle, categorized as a moderate increase. The findings suggest that the PBL model effectively improves the learning process and enhances students' MRS, fostering a more engaging and interactive learning environment.